Brittle and semi-brittle behaviours of a carbonate rock: influence of water and temperature. Issue 1 (26th April 2016) - Nicolas, A.; Fortin, J.; Regnet, J.B.; Dimanov, A.; Guéguen, Y.
Abstract: Inelastic deformation can either occur with dilatancy or compaction, implying differences in porosity changes, failure and petrophysical properties. In this study, the roles of water as a pore fluid, and of temperature, on the deformation and failure of a micritic limestone (white Tavel limestone, porosity 14.7 per cent) were investigated under triaxial stresses. For each sample, a hydrostatic load was applied up to the desired confining pressure (from 0 up to 85 MPa) at either room temperature or at 70 °C. Two pore fluid conditions were investigated at room temperature: dry and water saturated. The samples were deformed up to failure at a constant strain rate of ∼10 −5 s −1 . The experiments were coupled with ultrasonic wave velocity surveys to monitor crack densities. The linear trend between the axial crack density and the relative volumetric strain beyond the onset of dilatancy suggests that cracks propagate at constant aspect ratio. The decrease of ultrasonic wave velocities beyond the onset of inelastic compaction in the semi-brittle regime indicates the ongoing interplay of shear-enhanced compaction and crack development. Water has a weakening effect on the onset of dilatancy in the brittle regime, but no measurable influence on the peak strength. Temperature lowers the confining pressure at which the brittle–semi-brittle transition is observed but does not change the stress states at the onset of inelastic compaction and at the post-yield onset of dilatancy.